Post-Replication Repair Suppresses Duplication-Mediated Genome Instability - Putnam, Christopher D.; Hayes, Tikvah K.; Kolodner, Richard D. (PLOS Genetics, 2010)
Author Summary Genome instability is a hallmark of many cancers and underlies many inherited disorders that cause a predisposition to cancer. The human genome has many different types of duplicated sequences that can lead to genome instability by recombination-mediated pathways. We previously discovered that duplication-mediated chromosomal rearrangements are suppressed by a number of pathways. Some of these pathways were specific to rearrangements between genomic duplications. Here, we have performed a detailed analysis of pathways dependent upon RAD6, and have discovered that the error-free branch of post-replication repair (PRR) either is as an alternative to homologous recombination or prevents the generation of homologous recombination intermediates. Both of these functions could lead to genomic instability in the context of genomes containing substantial amounts of duplications. The extreme sensitivity of our assay to post-replication repair defects reveals substantial complexity in the interaction of PRR defects, suggesting the presence of many alternative PRR pathways. Together, the results emphasize the importance for appropriately balancing different repair pathways to maintain global genomic stability and highlight a number of defects that could underlie genome instabilities in some cancers.